Primerjava kinematike hoje po tleh in kinematike dveh različnih načinov krmiljenja vrtečega se tekočega traku - Pavčič, Janez (Informatica Medica Slovenica, 2015)
We developed a rotating treadmill (RT) which is used for training of dynamic stability in straight walking and walking while turning. Angular velocity of the RT can be controlled by the user in two ways: through movement of pelvis in medio-lateral direction or through rotation of the pelvis in the transversal plane. We conducted a study examining which method of angular velocity control yields kinematics that is similar to the kinematics of over-ground turning. Kinematic data of the feet, pelvis and torso in the transversal plane were captured with inertial sensors (Xsens). To establish the degree of similarity between both approaches of controlling the angular velocity and over-ground turning, we calculated intraclass correlation coefficients. Results indicate similarity of kinematics between the two control methods and over-ground walking.
Keywords: Biomechanical phenomena; Biomechanics; biomehanika; biomehanski pojavi; Gait; hoja; rehabilitacija; Rehabilitation; Walking